Indian Mass Media and the Politics of Change - Edited By Somnath Batabyal; Angad Chowdhry; Meenu Gaur and Matti Pohjonen (New Delhi Routledge Taylor and Francis Group, 2011)
"India has been the focus of international attention in the past few years. Rhetoric concerning its rapid economic growth and the burgeoning middle classes suggests that something new and significant is taking place. Something has changed, we are told: India is shining, the elephant is rising, and the 21st century will be Indian. What unites these powerful re-imaginings of the Indian nation is the notion of change
Includes Index.
Keywords: Mass Media -- Mass Media--Political Aspects -- India